A preliminary study on the incidence of fecal coliforms in food served by eight food-service establishments in the Municipality of Miag-ao - Ruiz, Joseph Michael S. (1996.)
Selected foods served in eight food-service establishments located in the town proper of the Municipality of Miag-ao were analyzed for the presence of fecal coliforms.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Enterobacteriaceae; Food